2018
DOI: 10.24321/2455.9318.201835
|View full text |Cite
|
Sign up to set email alerts
|

Study to Assess the Effect of Nursing Interventions on the Stress Level of Parents of Neonates Admitted to Neonatal Intensive Care Unit

Abstract: Introduction: A pre-experimental study to assess the effect of nursing interventions on the stress level of parents of neonates admitted to NICU in selected hospital. The primary objective of the study was to assess the effectiveness of nursing intervention on parental stress among the parents of neonates admitted to NICU. Methods:The present study was conducted among 30 parents of neonates admitted to NICU in a government hospital of New Delhi. The purposive sampling technique was applied. Parents were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…Mothers who directly breastfed their babies had significantly lower stress than mothers who did not (Chourasia et al, 2013). In the present study, a higher mean score of maternal stress was identified in the area of 'relationship with baby and parental role alteration' (Agrawal & Gaur, 2016;Chourasia et al, 2013;Kumar & Mallick, 2020;Rai & Rani, 2019;Varma et al, 2019), physiological domain, emotional domain and cognitive domain (Gurgani & Jogi, 2018;Reetha, 2020;Sidhu, 2016). Existing literature has stated that mothers experience higher levels of stress, depression due to child separation, child condition, equipment F I G U R E 3 Meta-analysis of maternal stress (PSS; NICU).…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Mothers who directly breastfed their babies had significantly lower stress than mothers who did not (Chourasia et al, 2013). In the present study, a higher mean score of maternal stress was identified in the area of 'relationship with baby and parental role alteration' (Agrawal & Gaur, 2016;Chourasia et al, 2013;Kumar & Mallick, 2020;Rai & Rani, 2019;Varma et al, 2019), physiological domain, emotional domain and cognitive domain (Gurgani & Jogi, 2018;Reetha, 2020;Sidhu, 2016). Existing literature has stated that mothers experience higher levels of stress, depression due to child separation, child condition, equipment F I G U R E 3 Meta-analysis of maternal stress (PSS; NICU).…”
Section: Discussionsupporting
confidence: 44%
“…Twelve studies have reported that others experienced severe stress (Agrawal & Gaur, 2016;Ashwani et al, 2017;Chourasia et al, 2013;Das & Krishna, 2020;Ganguly et al, 2020;Kumar & Mallick, 2020;Mulla & Patel, 2021;Niranjan et al, 2015;Patil, 2014;Rai & Rani, 2019;Reetha, 2020;Varma et al, 2019). Five studies have reported that mothers experienced a moderate level of stress (Sheeba & Prabhu T, 2019;Gurgani & Jogi, 2018;Rajalakshmi & Kalavathi, 2017;Sharma, 2019;Sidhu, 2016). Two studies have reported that mothers experienced mild stress levels during neonatal admission to the NICU (Shanmugam & Ramachandra, 2015;Vinod, 2017).…”
Section: Maternal Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the identification of stress and coping strategies mothers use still focuses a lot on when the baby is in the NICU (Gurgani & Jogi, 2018;Patil, 2014;Paul et al, 2018;Rajalakshmi & Kalavathi, 2017Sharma, 2019Tajalli et al, 2022). In contrast, stress and coping strategies for mothers when caring for premature babies at home are still under-researched (de Castro Pereira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%